Development of Flat Burr Coffee Grinding Machine for Small and Medium Enterprises Scale - Warandi, Rofandi Rori Aditiar; Furqon , Maulana; Gandara, Dadang; Yudhi, Taufik; Rosadi, Ade; Santoso, Santoso; Setyawan, Azis Budi; Noor, Subardiya; Samsu, Samsu; Rahayuningtyas , Ari (Journal of Applied Agricultural Science and Technology, 2024)
This study was conducted to develop an improved coffee grinder tailored for small and medium enterprises (SMEs) to address challenges due to limited resources. The development phase included a broad description, sizing, defining main components, developing technical drawings, manufacturing, and conducting functional tests. The machine had an overall dimension of 743 mm in length, 367 mm in width, and 580 mm in height. It was powered by a 1 HP induction motor with a rotation speed of 1400 rotations per minute (RPM) and a shaft diameter of 19 mm. The prototype achieved a grinding capacity of 23.8 kg/h for acceptable coffee grounds while maintaining a constant grind size, essential for achieving the best flavor and aroma. However, the noise level reached 86.5 dB, requiring hearing protection for prolonged usage. Future investigations should focus on exploring alternative materials and developing noise mitigation strategies, as noise reduction efforts can enhance operator physical and mental health in the coffee production process.